A review on Oxidative Stress and Nano-medicine: Emerging Strategies for Disease Management - Chetehouna, Sara; Boulaares, Islam; Frahtia, Ahlem; Zouari, Wafa Ahmed; Derouiche, Samir (Journal of Neonatal Surgery, 2025)
Oxidative stress results from an imbalance between the production of reactive oxygen species (ROS) and the antioxidant defense system, contributing to the onset and progression of several chronic and degenerative diseases. Nanoparticles (NPs), owing to their unique physicochemical properties, have emerged as both modulators of oxidative stress and therapeutic agents. Metal and metal oxide nanoparticles such as manganese, selenium, and zinc exhibit intrinsic antioxidant activities by mimicking enzymatic systems like superoxide dismutase and catalase, while green-synthesized nanoparticles provide synergistic bioactivity through plant-derived compounds. These "nanozymes" not only scavenge ROS but also enhance bioavailability, stability, and targeted delivery of antioxidants. This review discusses the dual role of nanoparticles in inducing and counteracting oxidative stress, the mechanisms of ROS generation, organelle-specific damage, and biological consequences including DNA damage, inflammation, and apoptosis. Furthermore, we highlight the therapeutic applications of nanoparticles in neurodegenerative disorders, cancer, diabetes, and reproductive dysfunctions, along with their challenges related to toxicity, dose-dependent effects, and biocompatibility. By integrating nanotechnology with redox biology, nanoparticles represent a promising yet complex platform for combating oxidative stress–mediated diseases, requiring careful optimization to balance efficacy and safety.